A covalent organic framework nanomaterial and its preparation method and application

A vinyl-rich triazine core COFs nanomaterial, combined with carbon nanotubes or RuCl3, addresses conductivity issues in COFs, enhancing their performance in energy storage and catalysis by improving conductivity and structural stability.

CN118206771BActive Publication Date: 2025-01-03HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410285911.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-13
Publication Date
2025-01-03
Estimated Expiration
2044-03-13

AI Technical Summary

Technical Problem

Existing covalent organic frameworks (COFs) suffer from poor conductivity, which limits their performance as electrocatalysts and energy storage materials due to their polymer nature, and their morphology affects catalytic performance by restricting mass transfer.

Method used

A covalent organic framework nanomaterial with vinyl-rich side chains and a triazine core is synthesized through a solvothermal method, combined with carbon nanotubes or RuCl3 to enhance conductivity and introduce functional groups for improved catalytic and energy storage applications.

Benefits of technology

The composite materials exhibit enhanced electrical conductivity and stability, enabling effective use in Li-S batteries and catalysts, with potential for improved energy storage and conversion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118206771B_ABST
    Figure CN118206771B_ABST
Patent Text Reader

Abstract

The embodiments of the present application relate to a covalent organic framework nanomaterial and its preparation method and application, belonging to the field of nanomaterial technology. The preparation method of the covalent organic framework nanomaterial of the embodiment of the present application comprises the following steps: (1) dissolving an aldehyde monomer, a triazine methyl monomer and a catalyst in a solvent, and obtaining a mixed solution by ultrasonic treatment; (2) removing air from the mixed solution by freezing, vacuumizing and thawing, and then sealing the mixed solution with a flame, heating it, washing and drying it to obtain the COFs nanomaterial. The covalent organic framework (COFs) nanomaterial provided in the embodiment of the present application, which has a side chain rich in vinyl and a main body rich in triazine N atoms that can act as ligands, can realize the multifunctional application of the material through chemical modification of specific functional groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of nanomaterials, and in particular to a covalent organic framework nanomaterial and a preparation method and application thereof. Background Art

[0002] Improving the conversion and storage efficiency of renewable energy is an important environmental protection measure for modern society in the 21st century. One of the promising ways to solve the above problems is to use wind energy, solar energy, etc. to provide the required electricity, and use the electrocatalytic hydrogen evolution reaction (HER) to decompose water to achieve the conversion of renewable energy. Another method is to use secondary battery energy storage devices such as lithium-sulfur (Li-S) batteries with advantages such as high energy density, low production cost and wide sources to expand and develop the field of electrochemical energy storage technology. In this regard, covalent organic frameworks (COFs) based on triazine units to construct a fully conjugated structure show properties such as large specific surface area and moderate conductivity that are conducive to π electron transmission and are considered to be candidates for host materials for energy conversion and storage.

[0003] COFs are ordered structures constructed with atomic precision from organic monomers, connected by covalent bonds, with good thermal stability, large specific surface area and low skeleton density, large π-π conjugated system and open regular pores, which are conducive to the transfer of electrons in the material and can be applied to gas storage and adsorption separation, catalysis, energy, chemical sensing and biomedicine. However, the morphology of COF will directly affect its catalytic performance by promoting mass transfer, but COF as a polymer of organic molecules inevitably has poor conductivity, which is also an important factor restricting COF as a HER catalyst. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a covalent organic framework nanomaterial and a preparation method and application thereof. The covalent organic framework (COFs) nanomaterial whose side chains are rich in vinyl groups and whose main body is rich in triazine N atoms that can act as ligands can achieve multifunctional applications of the material through chemical modification of specific functional groups, and can effectively overcome the defects of the above-mentioned prior art.

[0005] The first aspect of the embodiment of the present application provides a method for preparing a covalent organic framework nanomaterial, comprising the following steps:

[0006] (1) dissolving an aldehyde monomer, a triazine methyl monomer and a catalyst in a solvent, and subjecting the mixture to ultrasonic treatment to obtain a mixed solution;

[0007] (2) The mixed solution is subjected to freezing, vacuuming, and thawing treatments to remove air, and then flame-sealed and heated, and then washed and dried to obtain COFs nanomaterials.

[0008] At present, the composite materials of COFs and other materials (such as metal covalent organic frameworks, metal oxides and MXene, etc.) can not only make full use of the advantages of COFs materials themselves, but also effectively improve the application performance of COFs materials in catalysis, energy storage and other fields. Therefore, it is imperative to design COFs materials with designability, tailorability and easy functionalization for the synthesis of composite materials.

[0009] Based on this, the present application has designed a highly conjugated COFs nanomaterial with a vinyl-rich side chain and a triazine core as the main body. The composite material of the COFs nanomaterial chemically bonded to the amino carbon nanotubes improves the electrical conductivity. The rich vinyl in the composite material can be used as a template through the "reverse sulfurization" reaction in the positive electrode field of Li-S batteries. There is potential for application. In addition, the composite material obtained by the coordination of the COFs nanomaterial and RuCl3 has potential value in the field of catalysts. Therefore, from the perspective of COFs structural regulation, this application is of great significance to develop and improve the performance of this type of material in energy storage and conversion.

[0010] In some embodiments that may include the above embodiments, step (1) further comprises dissolving the aldehyde monomer and the amino carbon nanotubes CNTs in a solvent, ultrasonically treating them, then adding the triazine methyl monomer and the catalyst, and ultrasonically treating them again to obtain a mixed solution.

[0011] In some embodiments that may include the above embodiments, the following steps are also included:

[0012] (3) dissolving the COFs nanomaterial and ruthenium salt in an organic solvent, stirring at room temperature, centrifuging and washing, and drying to obtain a composite material of a covalent organic framework and ruthenium.

[0013] In some embodiments that may include the above embodiments, in step (2), the heating temperature is 120° C. and the heating time is 3 days; or

[0014] The freezing, vacuuming and thawing processes are each cycled three times; or

[0015] The washing is carried out alternately with tetrahydrofuran, methanol and acetone.

[0016] In some embodiments that may include the above embodiments, in step (1), the aldehyde monomers are all 1,4-divinylterephthalaldehyde; the triazine methyl monomers are all 1,3,5-trimethyl-2,4,6-triazine; the catalysts are all potassium hydroxide; and the solvents are all o-dichlorobenzene and n-butanol.

[0017] In some embodiments that may include the above embodiments, in step (1), the usage ratio of the aldehyde monomer:triazine methyl monomer:catalyst:solvent is 139.7 mg:61.58 mg:84 mg:10 ml; wherein the volume ratio of o-dichlorobenzene:n-butanol is 3:7.

[0018] In some embodiments that may include the above embodiments, in step (1), the dosage ratio of the aldehyde monomer: amino carbon nanotubes: triazine methyl monomer: catalyst: solvent is 28 mg: 40 mg: 12 mg: 16.8 mg: 2 ml; wherein the volume ratio of o-dichlorobenzene: n-butanol is 0.6:1.4.

[0019] In some embodiments that may include the above embodiments, in step (3), the stirring time is 8 hours; and

[0020] The organic solvent is methanol; and

[0021] The ruthenium salt is RuCl3; and

[0022] The dosage ratio of the COFs nanomaterial: RuCl3: methanol is 10 mg: 5 mg: 3 ml.

[0023] The second aspect of the embodiments of the present application also provides COFs nanomaterials obtained by the above-mentioned preparation method, or a composite material of carbon nanotubes and covalent organic frameworks obtained by the above-mentioned preparation method, or a composite material of covalent organic frameworks and RuCl3 obtained by the above-mentioned preparation method.

[0024] The third aspect of the embodiments of the present application also provides the use of the composite material of the above-mentioned COFs nanomaterial or carbon nanotubes and covalent organic framework or the composite material of covalent organic framework and RuCl3 in electrolysis of water.

[0025] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0026] 1. This application adopts a simple solvothermal method to design a new COFs nanomaterial with a triazine core containing vinyl groups in the side chain and a highly conjugated main framework.

[0027] 2. In the present application, COFs nanomaterials and amino carbon nanotubes are prepared by condensation reaction, and the obtained composite material has a more stable structure; and carbon nanotubes are introduced into this composite material to enhance the conductivity of the composite material. At the same time, the abundant vinyl groups in the COFs skeleton can undergo "reverse vulcanization" reaction and show the application value of Li-S battery positive electrode.

[0028] 3. In the present application, COFs nanomaterials and RuCl3 are prepared by coordination, and the obtained composite material structure introduces metal ions while maintaining the morphology of COFs nanomaterials, and has the potential for catalyst application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 Infrared spectra of COFs, COF@CNT and COF@Ru;

[0031] Figure 2 Powder X-ray diffraction patterns of COFs, COF@CNT and COF@Ru;

[0032] Figure 3 The nitrogen adsorption-desorption curve and pore size distribution curve of COFs;

[0033] Figure 4 The nitrogen adsorption-desorption curve and pore size distribution curve of COF@CNT;

[0034] Figure 5 The nitrogen adsorption-desorption curve and pore size distribution curve of COF@Ru;

[0035] Figure 6 (a), (b) and (c) are scanning electron micrographs of COFs, COF@CNT and COF@Ru, respectively. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0037] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.

[0038] In the following examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0039] Example 1

[0040] A method for preparing a covalent organic framework nanomaterial comprises the following steps:

[0041] (1) 139.7 mg of 1,4-divinylterephthalaldehyde, 61.58 mg of 1,3,5-trimethyl-2,4,6-triazine and 84 mg of potassium hydroxide were added to a mixed solvent of 3 mL of o-dichlorobenzene and 7 mL of n-butanol, and a mixed solution was obtained by ultrasonic treatment;

[0042] (2) The mixed solution was degassed by three freeze-vacuum-thaw cycles, flame-sealed and heated at 120° C. for 3 days. The obtained product was washed with tetrahydrofuran, methanol and acetone, and dried to obtain COFs powder.

[0043] The chemical reaction formula for the preparation of the above COFs nanomaterials is as follows:

[0044]

[0045] Example 2

[0046] A method for preparing a composite material of carbon nanotubes and a covalent organic framework comprises the following steps:

[0047] (1) 28 mg of 1,4-divinylterephthalaldehyde and 40 mg of amino carbon nanotubes were dissolved in a mixed solvent of 0.6 mL of o-dichlorobenzene and 1.4 mL of n-butanol, and then 12 mg of 1,3,5-trimethyl-2,4,6-triazine and 16.8 mg of potassium hydroxide were added, and then the mixture was treated with ultrasound again to obtain a mixed solution;

[0048] (2) The mixed solution was degassed by three freeze-vacuum-thaw cycles, flame-sealed and heated at 120° C. for 3 days. The obtained product was washed with tetrahydrofuran, methanol and acetone, and dried to obtain COF@CNT powder.

[0049] Example 3

[0050] A method for preparing a composite material of a covalent organic framework and ruthenium comprises the following steps:

[0051] (1) 139.7 mg of 1,4-divinylterephthalaldehyde, 61.58 mg of 1,3,5-trimethyl-2,4,6-triazine and 84 mg of potassium hydroxide were added to a mixed solvent of 3 mL of o-dichlorobenzene and 7 mL of n-butanol, and a mixed solution was obtained by ultrasonic treatment;

[0052] (2) the mixed solution was degassed by three freeze-vacuum-thaw cycles, flame-sealed and heated at 120° C. for 3 days, and the obtained product was washed with tetrahydrofuran, methanol and acetone, and dried to obtain COFs powder;

[0053] (3) 10 mg of COFs powder and 5 mg of RuCl3 were added to a flask containing 3 mL of methanol, stirred at room temperature for 8 h, centrifuged and washed, and placed in an oven to dry to obtain a COF@Ru composite material.

[0054] Application Examples

[0055] See also Figure 1 The COFs, COF@CNT and COF@Ru prepared in Examples 1-3 were subjected to infrared spectroscopy test and analysis. The same position of the -C=C- functional group absorption peak in the infrared spectra before and after compounding in the figure can determine that the composite material does not change the basic skeleton of the original COFs.

[0056] See also Figure 2 , COFs, COF@CNT and COF@Ru prepared in Examples 1-3 were subjected to powder X-ray diffraction analysis. The PXRD spectrum of COFs showed peaks of covalent organic framework at 4.72° and 23.5°, indicating the successful preparation of new COFs. Both COF@CNT and COF@Ru materials retained the peak of COFs at 4.72°, indicating that the skeleton of the original COFs was retained after the composite material was formed.

[0057] See also Figure 3 The COFs prepared in Example 1 of the present application were subjected to nitrogen adsorption and desorption tests using a fully automated specific surface area and porosity analyzer. The specific surface area was calculated to be 815 m 2 .g -1 The pore size of COFs calculated by nonlocal density functional theory is mainly distributed at 1.55 nm.

[0058] See also Figure 4 The COF@CNT prepared in Example 2 of the present application was subjected to nitrogen adsorption and desorption test using a fully automated specific surface area and porosity analyzer. The specific surface area was calculated to be 450 m according to the Brunauer-Emmett-Teller (BET) theory. 2 .g -1 The pore size of COF@CNT calculated by nonlocalized density functional theory is mainly distributed at 1.6nm, and the composite of CNTs produces an excess of mesoporous structure at 4.6nm.

[0059] See also Figure 5 The COF@Ru prepared in Example 3 of the present application was subjected to nitrogen adsorption and desorption test using a fully automated specific surface area and porosity analyzer. The specific surface area was calculated to be 697 m according to the Brunauer-Emmett-Teller (BET) theory.2 .g -1 The pore size of COF@Ru calculated by nonlocal density functional theory is mainly distributed in 1.50nm.

[0060] See also Figure 6 (a), (b) and (c) are scanning electron micrographs of COFs, COF@CNT and COF@Ru, respectively. Scanning electron microscopy shows that the new COFs present a uniform nanoflower structure. COF@CNT shows that COF is uniformly coated on carbon nanotubes to form a uniform core-shell structure. COF@Ru retains the nanoflower morphology of the original COFs.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a composite material of carbon nanotubes and covalent organic framework, characterized in that: The following steps are involved: (1) dissolving an aldehyde monomer, a triazine methyl monomer and a catalyst in a solvent, and subjecting the mixture to ultrasonic treatment to obtain a mixed solution; (2) The mixed solution is subjected to freezing, vacuuming, and thawing treatments to remove air, and then flame-sealed and heated, and then washed and dried to obtain COFs nanomaterials; In step (2), the heating temperature is 120°C and the heating time is 3 days; or The freezing, vacuuming and thawing processes are each cycled three times; or The washing is carried out alternately using tetrahydrofuran, methanol and acetone; Step (1) further comprises dissolving the aldehyde monomer and the amino carbon nanotubes in a solvent, ultrasonically treating the solvent, then adding the triazine methyl monomer and the catalyst, and ultrasonically treating the solvent again to obtain a mixed solution; The aldehyde monomers are all 1,4-divinylterephthalaldehyde; and the triazine methyl monomers are all 1,3,5-trimethyl-2,4,6-triazine.

2. A method for preparing a composite material of a covalent organic framework and ruthenium, characterized in that: The following steps are involved: (1) dissolving an aldehyde monomer, a triazine methyl monomer and a catalyst in a solvent, and subjecting the mixture to ultrasonic treatment to obtain a mixed solution; (2) The mixed solution is subjected to freezing, vacuuming, and thawing treatments to remove air, and then flame-sealed and heated, and then washed and dried to obtain COFs nanomaterials; (3) dissolving the COFs nanomaterial and ruthenium salt in an organic solvent, stirring at room temperature, centrifuging and washing, and drying to obtain a composite material of a covalent organic framework and ruthenium; The aldehyde monomers are all 1,4-divinylterephthalaldehyde; and the triazine methyl monomers are all 1,3,5-trimethyl-2,4,6-triazine.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the catalyst is potassium hydroxide.

4. The preparation method according to claim 1 or 2, characterized in that: In step (1), the dosage ratio of the aldehyde monomer: triazine methyl monomer: catalyst: solvent is 139.7 mg: 61.58 mg: 84 mg: 10 ml; the solvents are o-dichlorobenzene and n-butanol, wherein the volume ratio of o-dichlorobenzene: n-butanol is 3:

7.

5. The preparation method according to claim 1, characterized in that: In step (1), the dosage ratio of the aldehyde monomer: amino carbon nanotubes: triazine methyl monomer: catalyst: solvent is 28 mg: 40 mg: 12 mg: 16.8 mg: 2 ml; the solvents are o-dichlorobenzene and n-butanol, wherein the volume ratio of o-dichlorobenzene: n-butanol is 0.6:1.

4.

6. The preparation method according to claim 2, characterized in that: In step (3), the stirring time is 8 h; and The organic solvent is methanol; and The ruthenium salt is RuCl3; and The dosage ratio of the COFs nanomaterial: RuCl3: methanol is 10 mg: 5 mg: 3 ml.

7. A composite material of carbon nanotubes and a covalent organic framework obtained by the preparation method of claim 1 or a composite material of a covalent organic framework and ruthenium obtained by the preparation method of claim 2.

8. Use of the composite material of carbon nanotubes and covalent organic framework or the composite material of covalent organic framework and ruthenium according to claim 7 in electrolysis of water.